The lung proteome in HIV-associated obstructive lung disease - Sarah Samorodnitsky; Danielle Weise; Eric F. Lock; Ken M. Kunisaki; Alison Morris; Janice M. Leung; Monica Kruk; Laurie Parker; Pratik Jagtap; Timothy J. Griffin; Chris H. Wendt (ERJ Open Research)
Rationale Obstructive lung disease is increasingly common among persons living with HIV (PLWH). There are currently no validated biomarkers that identify individuals at risk of developing obstructive lung disease (OLD), and specific mechanisms contributing to HIV-associated OLD remain elusive, independent of smoking. We sought to identify biomarkers and biological pathways associated with OLD using a broad proteomic approach. Methods We performed tandem mass tagging and mass spectrometry (MS) analysis on bronchoalveolar lavage fluid samples from persons living with HIV with OLD (n=26) and without OLD (n=26). We combined untargeted MS with a targeted SomaScan aptamer-based approach. We used Pearson correlation tests to identify associations between each protein and lung function (forced expiratory volume in 1 s (FEV1) % pred). We adjusted for multiple comparisons using a false discovery rate adjustment. Significant proteins were entered into a pathway over-representation analysis. Protein-driven endotypes were constructed using K-means clustering. Measurements and main results We identified over 3800 proteins by MS and identified 254 proteins that correlated with FEV1 % pred when we combined the MS and SomaScan proteomes when adjusting for smoking status. Pathway analysis revealed cell adhesion molecules as significant. Conclusions Protein expression differs in the lung of PLWH and decreased lung function (FEV1 % pred). Pathway analysis reveals cell adhesion molecules having potentially important roles in this process.